The World Health Organization trauma checklist versus Trauma Team Time‐out: A perspective. (13th May 2019) - Fitzgerald, Mark; Reilly, Stephanie; Smit, De Villiers; Kim, Yesul; Mathew, Joseph; Boo, Ellaine; Alqahtani, Abdulrahman; Chowdhury, Sharfuddin; Darez, Ahamed; Mascarenhas, JMA Bruno; O'Keeffe, Francis; Noonan, Michael; et al.
Abstract: Time‐out protocols have reportedly improved team dynamics and patients' safety in various clinical settings – particularly in the operating room. In 2016, the World Health Organization (WHO) introduced a Trauma Care checklist, which outlines steps to follow immediately after the primary and secondary surveys and prior to the team leaving the patient. The WHO Trauma Care checklist's main perceived benefit is the prompting of clinicians to complete trauma admissions as per evidence‐based guidelines. The WHO Trauma Care checklist, while likely to be successful in reducing errors of omission related to hospital admission, may be limited in its ability to reduce errors that occur in the initial 30 min of trauma reception – when most of the life‐saving decisions are made. To address this limitation a Trauma Team Time‐out protocol is proposed for initial trauma resuscitation, targeting the critical first 30 min of hospital reception.